Քաղաքացիական հասարակության արդի հայեցակարգերը ժողովրդավարացման դիսկուրսի համատեքստում - Թումանյան, Գագիկ (Bulletin of Yerevan University G: Economics, 2017)
As we know nowadays in many publications of social sciences, as well as in mass media and public discourse, the idea of civil society often associated with the process of democratization. Thus, in the processes of democratization the limitations of liberalistic paradigm, which dominates in CS sphere, actualize the extension of organizational framework of the CS by combining the critical and analytical potential of liberal democratic discourse with actionalistic and functional meanings, which are crucial in neoclassical conceptions of CS. The model, which is elaborated through this synthesis, will promote a formulation of new mechanisms between CS and governmental institutions, which in turn will increase CS influence on the process of democratization of the governmental policy.
Keywords: civil society, power, democratization, neoclassicism, liberal democracy, discourse, solidarity, social capital, communicative power, rationality